Щодо умов просторового колапсу в нескінченній системі бозе-частинок - Grinyuk, B.E.; Bugaev, K.A. (Publishing house "Academperiodika", 2021)
Using the variational principle, we show that the condition of spatial collapse in a Bose gas is not determined by the value of the scattering length of the interaction potential between particles contrary to the result following from the Gross–Pitaevskii equation, where the collapse should take place at a negative scattering length.